LONGITUDINAL MONITORING OF INFLAMMATORY BOWEL DISEASE ACTIVITY USING WEARABLE DEVICES THROUGH INFLAMMATORY MARKERS IN SWEAT - Hirten, Robert; Lin, Kai-chun; Whang, Jessica; Shahub, Sarah; Sardesai, Abha; Helmus, Drew; Muthukumar, Sriram; Sands, Bruce; Prasad, Shalini (Inflammatory bowel diseases, 2023)
Abstract BACKGROUND Current methods to monitor inflammatory bowel disease (IBD) activity, such as colonoscopy, blood and stool markers, or imaging, are suboptimal and rely on single timepoint assessments that are inconvenient, expensive, or invasive. Wearable devices are a highly scalable mobile health technology that can non-invasively, continuously, and accurately monitor several physiological parameters that have been linked to flare in IBD. We performed a pilot feasibility study in subjects with IBD of a wearable device to monitor sweat-based inflammatory markers. METHODS Eligible participants were aged ≥ 18 years, diagnosed with IBD, admitted to the Mount Sinai Hospital for an IBD-related admission and had an elevated CRP (>5 mg/L). The sweat sensing device was worn by subjects to continuously measure the inflammatory markers C-reactive protein (CRP), tumor necrosis factor (TNF)α, and interleukin-6 (IL-6). The immunoassay on the sweat sensor was developed by immobilizing a specific capture probe antibody to capture CRP, TNFα and IL-6 in sweat. Data were transmitted from the device via Bluetooth to the cloud server. Sensor response was measured using impedance spectroscopy. Serum samples were collected daily. To evaluate the relationship between inflammatory markers in the sweat and serum, the Pearson correlation coefficient was calculated between longitudinal sweat measurements and serum CRP, TNFα and IL-6 levels. This was calculated for each subject with 2 or more consecutive serum values. The coefficient of variation was then calculated for each inflammatory marker. RESULTS A total of 16 subjects were enrolled. The sweat sensor device demonstrated the ability to measure in sweat CRP in the range of 525 to 1175.38 pg/ml, IL-6 in the range of 0.45 to 3.14 pg/ml, and TNFα in the range of 10.22 to 11.32 pg/ml. These measurements were correlated to their serum levels which were in the range of 2,200,000 to 12,7800,000 ug/ml for CRP, 0.68 to 31.66 pg/ml for IL-6, and 0.15 to 15.01 pg/ml for TNFα. The Pearson correlation coefficients between sweat and serum readings for CRP, IL-6 and TNFα are presented in Table 1. The coefficient of variation for CRP is 16.2% (mean 33,6863.14; standard deviation [std] 54,654.71), IL-6 is 19.5% (mean 33.23; std 7.06), and TNFα is 16.3% (mean 2.37; std 0.39). Figure 1 demonstrates temporal serum and sweat trends in a participant. Figure 1. Temporal trend of CRP, IL-6 and TNFα in the sweat and serum in a participant with Crohn’s disease. Table 1. The correlation between CRP, IL-6 and TNFα in the serum to the sweat in participants. CONCLUSION Longitudinally collected sweat CRP, IL-6 and TNFα, measured using a wearable device, correlate with serum measurements. This work is the first demonstration of continuous, non-invasive methods to longitudinally monitor inflammatory markers in sweat, and suggests the feasibility of using a non-invasive sweat-sensing wearable device to monitor IBD disease activity.